Quantitative Systems Pharmacology Model-Based Predictions of Clinical Endpoints to Optimize Warfarin and Rivaroxaban Anti-Thrombosis Therapy - Hartmann, Sonja; Biliouris, Konstantinos; Lesko, Lawrence J.; Nowak-Göttl, Ulrike; Trame, Mirjam N. (Frontiers in Pharmacology, 2020)
Background: Tight monitoring of efficacy and safety of anticoagulants such as warfarin is imperative to optimize the benefit-risk ratio of anticoagulants in patients. The standard tests used are measurements of prothrombin time (PT), usually expressed as international normalized ratio (INR), and activated partial thromboplastin time (aPTT). Objective: To leverage a previously developed quantitative systems pharmacology (QSP) model describing the human coagulation network to predict INR and aPTT for warfarin and rivaroxaban, respectively. Methods: A modeling and simulation approach was used to predict INR and aPTT measurements of patients receiving steady-state anticoagulation therapy. A previously developed QSP model was leveraged for the present analysis. The effect of genetic polymorphisms known to influence dose response of warfarin (CYP2C9, VKORC1) were implemented into the model by modifying warfarin clearance (CYP2C9 *1: 0.2 L/h; *2: 0.14 L/h, *3: 0.04 L/h) and the amount of available vitamin K (VKORC1 GA: -22% from normal vitamin K amount; AA: -44% from normal vitamin K amount). Virtual patient populations were used to assess the ability of the model to accurately predict routine INR and aPTT measurements from patients under long-term anticoagulant therapy. Results: The introduced model accurately described the observed INR of patients receiving long-term warfarin treatment. The model was able to demonstrate the influence of genetic polymorphisms of CYP2C9 and VKORC1 on the INR measurements. Additionally, the model was successfully used to predict aPTT measurements for patients receiving long-term rivaroxaban therapy. Conclusion: The model accurately predicted INR and aPTT measurements observed during routine therapeutic drug monitoring and may be used as a tool during clinical practice to predict efficacy and safety of anticoagulants and help optimize anti-thrombotic therapy when used as a model-based precision dosing tool.